Norrin Protected Blood–Brain Barrier Via Frizzled-4/β-Catenin Pathway After Subarachnoid Hemorrhage in Rats. Issue 2 (February 2015) - Chen, Yujie; Zhang, Yang; Tang, Junjia; Liu, Fei; Hu, Qin; Luo, Chunxia; Tang, Jiping; Feng, Hua; Zhang, John H.
<x xml:space="preserve">Abstract</x> Background and Purpose— Norrin and its receptor Frizzled-4 have important roles in the blood–brain barrier development. This study is to investigate a potential role and mechanism of Norrin/Frizzled-4 on protecting blood–brain barrier integrity after subarachnoid hemorrhage (SAH). Methods— One hundred and seventy-eight male Sprague–Dawley rats were used. SAH model was induced by endovascular perforation. Frizzled-4 small interfering RNA was injected intracerebroventricularly 48 hours before SAH. Norrin was administrated intracerebroventricularly 3 hours after SAH. SAH grade, neurological scores, brain water content, Evans blue extravasation, western blots, and immunofluorescence were used to study the mechanisms of Norrin and its receptor regulation protein TSPAN12, as well as neurological outcome. Results— Endogenous Norrin and TSPAN12 expression were increased after SAH, and Norrin was colocalized with astrocytes marker glial fibrillary acidic protein in cortex. Exogenous Norrin treatment significantly alleviated neurobehavioral dysfunction, reduced brain water content and Evans blue extravasation, promoted β-catenin nuclear translocation, and increased Occludin, VE-Cadherin, and ZO-1 expressions. These effects were abolished by Frizzled-4 small interfering RNA pretreated before SAH. Conclusions— Norrin protected blood–brain barrier integrity and improved neurological outcome after SAH, and the action of Norrin appeared mediated by Frizzled-4 receptor activation, which promoted β-catenin nuclear translocation, which then enhanced Occludin, VE-Cadherin, and ZO-1 expression. Norrin might have potential to protect blood–brain barrier after SAH.